SOCIAL MEDIA MARKETING ACTIVITIES ON REPURCHASE INTENTION: MEDIATION BY PERCEIVED VALUE, E-WOM, AND TRUST - Mulya, Jumiatul -; Dwita, Vidyarini (JURNAL ECONOMICA : Research of Economic And Economic Education, 2024)
This study proposes a model in which SMMA influences repurchase intention which is mediated by perceived value, e-wom, and trust. The sample in this study amounted to 155 people. The results of the study reveal that SMMA has a positive and significant effect on perceived value, repurchase intention, e-WOM, and trust. Perceived value and trust have a positive and significant effect on repurchase intention. e-WOM has no significant effect on repurchase intention. SMMA has a positive and significant effect on repurchase intention which is mediated by perceived value and trust. SMMA has no significant effect on repurchase intention mediated by e-WOM.